(untitled) (The International Journal for Scientific Research, 2025)
This research aimed to identify the degree of science female teachers’ awareness of active learning strategies and its relationship to the self-regulated learning skills of their female students in the intermediate stage in Bisha. To achieve the objectives of this research, the researcher used a questionnaire for active learning strategies for female teachers, and a questionnaire for self-regulated learning skills for female students, both of which were prepared by previous researchers and adopted by the researcher after codifying them on the research community. The research sample consisted of (30) science female teachers, and (60) female students in the intermediate stage. The descriptive correlational approach was used to reach the results of the research with the use of statistical methods represented in frequencies, frequencies, arithmetic mean, and Cronbach’s alpha and Pearson’s coefficient in processing the data statistically according to the research questions. The results revealed a high degree of awareness of active learning strategies among intermediate school science female teachers, which was at a high degree, and the degree of intermediate school female students’ possession of self-regulated learning skills in the science course was very high. The results also showed that there was a correlation between the awareness of active learning strategies among science female teachers in the intermediate stage and the self-regulated learning skills of their students at the level of (0.05).